Parametric optimization of multi-pass electron beam melting for molybdenum alloy containing 47.5 wt% rhenium. (June 2023) - Guo, Wenbin; Li, Geping; Bair, Dampilon; Chen, Feipeng; Zhang, Yifei; Li, Songbin; Sun, Liyuan; Han, Fuzhou; Ali, Muhammad; Ren, Jie
Abstract: In this study, the effects of multi-pass electron beam melting (EBM) processes under vacuum condition on microstructure and mechanical behavior of a molybdenum alloy containing 47.5 wt% rhenium were systematically investigated. Nine experimental designs were performed to improve the surface quality and minimize the defects. Results showed that beam power, scan speed, processing step and penetration depth played a critical role in the specific energy density function, which would further influence the porosity and microhardness. Meanwhile, specific energy density was significantly influenced by beam power at higher scan speed (e.g. 15 mm/s) whereas it was mainly related to scan speed under lower beam power (e.g. 2 kW). With a processing step of 0.5 mm (half of the beam diameter), a continuous melt morphology and less porosity were obtained, indicating that a significant overlap between the scan tracks was beneficial for the optimization of microstructure. Microhardness results showed that mechanical performance can be improved with the reduction of porosity together with the increased specific energy density. Thus, a combination of 10 kW beam power, 2 mm/s scan rate and 0.5 mm processing step can realize surface optimization in melted plates through multi-pass EBM technique. Highlights: Multi-pass electron beam melting process is performed to optimize the microstructure of Mo-47.5Re alloy. The effect of energy input on porosity variation during melting process is discussed. The relationship between process parameters, resulting microstructure and microhardness is presented.